Anticancer properties of red beetroot hydro-alcoholic extract and its main constituent; betanin on colorectal cancer cell lines - Amir Saber; Nasim Abedimanesh; Mohammad-Hossein Somi; Ahmad Yari Khosroushahi; Shima Moradi (BMC, 2023)
Abstract Colorectal cancer (CRC) is the third most common type of cancer worldwide. Red beetroot (Beta vulgaris) contains Betanin as its major betacyanin, possessing wide proapoptotic effects. This study aimed to investigate the anticancer and pro-papoptotic effects of beetroot hydro-alcoholic extract (BHE) and betanin, on colorectal cancer cell lines. BHE and betanin were used to treat Caco-2 and HT-29 colorectal cancer cells. MTT assay, DAPI staining, and FACS-flow cytometry tests were used to determine the half-maximal inhibitory concentration (IC50) and apoptosis-inducing evaluations. Intended genes were assessed by real-time polymerase chain reaction (RT-PCR). The IC50 for HT-29 and Caco-2 cell lines were 92 μg/mL, 107 μg/mL for BHE, and 64 μg/mL, 90 μg/mL for betanin at 48 h, respectively. BHE and betanin significantly inhibited the growth of both cancer cell lines time and dose-dependently. DAPI staining and flow cytometry results revealed significant apoptosis symptoms in treated cancerous cell lines. The expression level of proapoptotic genes (BAD, Caspase-3, Caspase-8, Caspase-9, and Fas-R) in treated HT-29 and Caco-2 cells was higher than in untreated and normal cells. In contrast, the anti-apoptotic gene (Bcl-2) was significantly downregulated. BHE and betanin effectively inhibited cancer cell proliferation and induced apoptosis via the modification of effective genes.